2020
DOI: 10.1111/caim.12416
|View full text |Cite
|
Sign up to set email alerts
|

The IKEA effect in collective problem‐solving: When individuals prioritize their own solutions

Abstract: To improve problem‐solving performance, individuals can rely on social learning. This approach is constrained by an individual's social network, which influences the efficiency of the problem‐solving process. To date, research disagrees on what kind of network structure is preferable, providing support for efficient network structures, as well as for inefficient networks. However, studies implicitly assume that solvers always imitate superior solutions, an assumption that lacks empirical grounding. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The phase-coding method presented herein is based on individual contributions, so it may help to shed light on the optimal group composition (Kozlowski, 2015). Given that group problem-solving skills do not come naturally to all members (Bateman, 2005;Jadhav et al, 2014;Netland, 2016;Vuculescu et al, 2021) and that a 1 h KE-skill training was not found to greatly improve the process, it is time to craft and test different modes of sophisticated KE training on real-life groups (Oliva, 2019). Such interventions can benefit from visual representations for KE participants' learning and performance (Aoki, 2019) and may even be extended to similar studies of structured problem-solving approaches such as DMAIC and Quality Circles (De Mast and Lokkerbol, 2012;Rafaai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The phase-coding method presented herein is based on individual contributions, so it may help to shed light on the optimal group composition (Kozlowski, 2015). Given that group problem-solving skills do not come naturally to all members (Bateman, 2005;Jadhav et al, 2014;Netland, 2016;Vuculescu et al, 2021) and that a 1 h KE-skill training was not found to greatly improve the process, it is time to craft and test different modes of sophisticated KE training on real-life groups (Oliva, 2019). Such interventions can benefit from visual representations for KE participants' learning and performance (Aoki, 2019) and may even be extended to similar studies of structured problem-solving approaches such as DMAIC and Quality Circles (De Mast and Lokkerbol, 2012;Rafaai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral economists have proposed that people are subject to a so-called IKEA effect, whereby they attach greater value to products they make for themselves than to otherwise indiscernible goods. Recently, cognitive psychologist Tom Stafford (2021) has suggested that there may be an epistemic analog to this, a kind of epistemic IKEA effect (see also Vuculescu et al, 2021, for a related line of thought). In what follows, I use Stafford's suggestion to shed light on a thesis about epistemic value that I want to defend.…”
Section: Introductionmentioning
confidence: 99%